Equilibrium Modeling of Astaxanthin Extraction from Haematococcus pluvialis - Putri Restu Dewati; Rochmadi Rochmadi; Abdul Rohman; Avido Yuliestyan; Arief Budiman (Indonesian Journal of Chemistry, 2021)
Astaxanthin is a natural antioxidant, and the highest content of this compound is found in Haematococcus pluvialis microalgae. Microwave-assisted extraction (MAE) is one of the environmentally friendly extraction methods and has many advantages. This study aims to investigate the extraction of astaxanthin through the MAE method using various solvents. Several equilibrium models were proposed to describe this solid-liquid equilibrium. The solid-liquid extraction equilibrium parameters were determined by minimizing the sum of squares of errors (SSE), in which equilibrium constants were needed for scaling up purposes. Previously, the microalgae were pretreated with HCl to soften their cell walls in order to improve the extraction recovery. In this study, dichloromethane, acetone, methanol, and ethanol were used as the solvents for extraction. The astaxanthin concentration was determined by high-performance liquid chromatography (HPLC) and spectrophotometry. Astaxanthin was found to attain equilibrium at 57.42% recovery in a single-step extraction. Thus, several steps were required in sequence to obtain an optimum recovery. The experimental data were fitted to three equilibrium models, namely, Henry, Freundlich, and Langmuir models. The experimental data were well fitted to all the models for the extraction in dichloromethane, methanol, ethanol and acetone, as evident from the almost same SSE value for each model.